1973
DOI: 10.1021/ja00802a001
|View full text |Cite
|
Sign up to set email alerts
|

Entropies of solution of ions in water

Abstract: The entropies of solution of ions in water and the entropies of transfer from an ideal solution to aqueous solution have been obtained by assuming that the entropy of an ion in a crystal lattice is constant and independent of the lattice containing the ion and that the entropies of solution {i.e., solid to liquid) of Ph4As+ and Ph4Bare equal. The values are internally consistent and agree favorably with entropies of solution and entropies of transfer calculated from the entropies of hydration (gas to liquid) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 0 publications
1
66
1
Order By: Relevance
“…Therefore, the large sigmoidal wave was separated into two sections with the first being used to describe TB À IT and the second for UO 2 2 + IT. Conventional evaluation of LSVs or cyclic voltammograms (CVs) obtained from liquid j liquid systems is to calibrate the potential scale using the TATB assumption [29,30] and known IT potentials; this technique is analogous to an internal standard method and in the present case TMA + IT was used as an internal reference, D w o f8' = 0.160 V [31]. First the electrochemical cell is scanned, then a known concentration of internal standard is added, and the system is scanned again.…”
mentioning
confidence: 99%
“…Therefore, the large sigmoidal wave was separated into two sections with the first being used to describe TB À IT and the second for UO 2 2 + IT. Conventional evaluation of LSVs or cyclic voltammograms (CVs) obtained from liquid j liquid systems is to calibrate the potential scale using the TATB assumption [29,30] and known IT potentials; this technique is analogous to an internal standard method and in the present case TMA + IT was used as an internal reference, D w o f8' = 0.160 V [31]. First the electrochemical cell is scanned, then a known concentration of internal standard is added, and the system is scanned again.…”
mentioning
confidence: 99%
“…Wulff (1967) and Cox and Parker (1973) reported that the correlation developed by Powell and Latimer represented published values within 2-3 cal mol -1 K -1 . Laidler (1957) suggested that Powell and Latimer's relation did not take into account Born's theory for entropy changes for reactions of various ionic types and proposed a correlation for the entropy of an ion at infinite dilution as a function of the square of the ionic charge and the univalent radii.…”
Section: Entropy Estimation Techniquesmentioning
confidence: 80%
“…This means that the TATB assumption concerning the standard partial molar entropy adopted by Cox and Parker, (22) …”
Section: Discussionmentioning
confidence: 99%